The Prairie and Deliverance: A Futile Search for a “Paradise Regained” - Djuhertati Imam Muhni (Humaniora, 1998)
Through the fall of Adam and Eve, paradise was lost to human beings; the striving for its recovery never ends. The dream for a "paradise on earth" is a universal phenomenon which attracks writers. In this short essay I would attempt to show how two American novelists of different generations depict the futile effort to regain the lost paradise in this world. James Fenimore Cooper who wrotr The Prairie was born in the nineteenth century whereas James Dickey the writer of Deliverance was born in tyhe twentieth, yet both novelists deal with the tragic relationship between the ideal and the real. In their Respective novels, The Prairie and Deliverance, both James Fenimore Cooper and James Dickey describe humankind's futile search for a paradise regained. Both are bitter books, in the sense that the protagonists in each find out that wahat they are striving for is only an empty dream.